Evaluation of the Implementation of the School Encounter Literacy Program at SMA Negeri 1 Gunung Sari: A Case Study Based on the CIPP Model - Ati Rahmawati; Supardi Supardi (AS-SABIQUN, 2026)
This study is motivated by the limited empirical evaluation of encounter-based literacy programs at the senior high school level, despite their potential to strengthen students’ literacy competence and character development. This study aims to evaluate the implementation of the School Encounter Literacy Program at SMA Negeri 1 Gunung Sari using the CIPP evaluation model. A qualitative case study design was employed, involving 26 participants. Data were collected through semi-structured interviews, questionnaires, observations, and document analysis, and were analyzed using thematic analysis supported by descriptive quantitative scoring. The findings reveal that the program was contextually relevant as a strategic response to literacy stagnation and students’ low reading comprehension. The input dimension demonstrated relatively strong organizational readiness, reflected in the highest average score of 72.6%, particularly in material accessibility through digital platforms. However, the process dimension obtained the lowest score of 55.6%, indicating challenges related to implementation consistency, teacher attentiveness, and feedback mechanisms. The product evaluation showed generally positive outcomes, with an overall effectiveness score of 66.8%, indicating improvements in students’ storytelling confidence, literacy engagement, academic participation, and character development. The study concludes that encounter-based literacy programs can serve as effective educational innovations when literacy is positioned as a reflective social practice. This study extends the application of the CIPP model to literacy program evaluation and offers practical implications for strengthening teacher training, procedural monitoring, and character assessment instruments. Future research should employ longitudinal and multi-site designs to examine the sustainability and broader applicability of encounter-based literacy programs.